1997
DOI: 10.1016/s0006-3495(97)78647-8
|View full text |Cite
|
Sign up to set email alerts
|

Charge density-dependent strength of hydration and biological structure

Abstract: Small ions of high charge density (kosmotropes) bind water molecules strongly, whereas large monovalent ions of low charge density (chaotropes) bind water molecules weakly relative to the strength of water-water interactions in bulk solution. The standard heat of solution of a crystalline alkali halide is shown here to be negative (exothermic) only when one ion is a kosmotrope and the ion of opposite charge is a chaotrope; this standard heat of solution is known to become proportionally more positive as the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
1,239
3
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,161 publications
(1,309 citation statements)
references
References 87 publications
64
1,239
3
3
Order By: Relevance
“…Until rather recently, Na + ions were thought to be rather indifferent cations with respect to phospholipids, 94,95 and ion binding in general to take place only in the headgroup region. 28,30 During the past decade, however, this view has been challenged.…”
Section: Discussionmentioning
confidence: 99%
“…Until rather recently, Na + ions were thought to be rather indifferent cations with respect to phospholipids, 94,95 and ion binding in general to take place only in the headgroup region. 28,30 During the past decade, however, this view has been challenged.…”
Section: Discussionmentioning
confidence: 99%
“…Since sodium ions contain fewer electrons than chloride ions, our SAXS results suggest that water molecules are ''contracting'' locally more around acidic than around basic surface residues and that protein HS properties are a combined result of a residue-specific ionic interaction and structural changes of water molecules in their vicinity. Indeed, an important factor not taken into account by most SAXS/ SANS programs is the contribution of solvent ions in the vicinity of proteins, which may display concentrations that vary significantly from those in the bulk as a function of the local physicochemical protein surface properties (24,25). Recent MD simulations suggest that ions may either bind specifically and locally to oppositely charged protein surface residues (67,68) or accumulate at nonpolar surface patches (66) as a function of type (i.e., anions/cations) and size, an observation supported by SANS experiments with varying salt concentrations and type (5,33).…”
Section: Protein Hs Density and Ionic Composition Depend On The Surfamentioning
confidence: 99%
“…Increased water density in the first hydration shell (HS), as well as surface-specific differences in the organization of the hydration water, have been reported by MD simulations (17)(18)(19)(20) and have been described thermodynamically in terms of electrorestriction (21). MD studies involving nucleic acids (7,22,23) or proteins (24,25), as well as anomalous x-ray solution studies on proteins and nucleic acids (26,27), have revealed the specific recruitment of ions into their HSs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been argued that ammonium and sodium ions cannot form cyclo-complexes with amino acids in the same way as magnesium and other divalent cations such as Ca 2+ , 78 Na + , and K + are often viewed as roughly neutral. 95 Density functional theory calculations of the relative stability of gasphase complexes between metal ions and amino acids 96−98 have shown that the Gibbs energies of (ion−amino acid) systems are much less positive in the case of divalent ions than of monovalent ions. For instance, for (ion−arginine) complexes, 96 the values of the gas-phase Gibbs energies follow the order Ni 2+ (−1544 kJ mol −1 ) < Cu 2+ (−1404 kJ mol −1 ) < Zn 2+ (−1280 kJ mol −1 ) < Mg 2+ (−1028 kJ mol −1 ) < Ca 2+ (−660 kJ mol −1 ) < Li + (−328 kJ mol −1 ) <Na + (−225 kJ mol −1 ) < K + (−152 kJ mol −1 ), at T = 298.15 K.…”
Section: Simulationsmentioning
confidence: 99%